A Spiritual Lesson to be Taken from the Earthquake in Türkiye - HÜSEYIN ÇAKSEN (Pakistan Journal of Medical & Health Sciences, 2025)
About 50,000 earthquakes large enough to be noticed without the aid of instruments occur annually worldwide. Some 100 of these are large enough to cause substantial damage if centered near populated areas. Over the centuries, earthquakes have been responsible for millions of deaths and incalculable damage1. Lastly, Türkiye and Syria were rocked by two huge earthquakes with magnitudes of 7.7 and 7.6 (Mw), separated by just nine hours on February 6, 2023. After the catastrophe, tens of thousands of deaths occurred with countless others injured. While hundreds of thousands of patients including children injured in the earthquake were treated in the emergency departments and wards of many hospitals, some of them lost their lives. Earthquake victims are in need of shelter, clean water, food, medical and mental care, physical rehabilitation and psychosocial and economic support. Although many articles have been written about the effects of earthquakes on physical, mental, and social health, spiritual dimension of earthquakes has been frequently ignored. Here, we presented a spiritual lesson to be taken from the earthquake in order to draw attention to the spiritual dimension of the earthquake.